2011
DOI: 10.24059/olj.v15i2.174
|View full text |Cite
|
Sign up to set email alerts
|

Online Teacher Education: Exploring the Impact of a Reading and Literacy Program on Student Learning

Abstract: This study presents findings from an investigation of the impact of teachers who graduated from a fully online master’s degree program with training in pedagogy and a content-specialization in elementary reading and literacy (oERL) on reading achievement in a large urban public school system in the northwestern United States. The research team used a non-equivalent group design and matched pairs of teachers based on degree, grade-level taught, and teaching experience to construct the study on three years of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…The results of this study are supported by research conducted by (Weschke et al, 2011) with teachers as research objects trained to apply online learning. The results of the study state that the full online program aimed at training teachers can provide opportunities for teachers to gain knowledge of pedagogical content that can positively influence teaching effectiveness.…”
Section: B Correlation Between Teachers' Pedagogic Competence and Stsupporting
confidence: 71%
“…The results of this study are supported by research conducted by (Weschke et al, 2011) with teachers as research objects trained to apply online learning. The results of the study state that the full online program aimed at training teachers can provide opportunities for teachers to gain knowledge of pedagogical content that can positively influence teaching effectiveness.…”
Section: B Correlation Between Teachers' Pedagogic Competence and Stsupporting
confidence: 71%
“…The final study reported in this sub-section is Weschke, Barclay & Vandersall (2011) [104], who undertook a small-scale study of 31 elementary teachers who completed a fully online master's programme on pedagogy and literacy matched with a comparative sample of 39 teachers with an existing masters level qualification who did not complete the online programme. The study looked at the impacts on oral reading fluency of students as a measure of efficacy by undertaking 3828 student observations.…”
Section: Mixed Component Interventionsmentioning
confidence: 99%
“…Further, online learning creates accessible opportunities since it utilizes platforms that deliver information irrespective of time, place, and situational barriers (Kanuka & Nocente, 2003). Studies of online learning opportunities for teachers have identified positive effects and even changes in teachers' pedagogical and content knowledge, classroom practice, and student outcomes (Weschke & Barclay, 2011). In fact, even teachers in traditional settings seem to prefer the Internet for their professional learning (Charalambousa & Ioannou, 2011;Kao, Wu, & Tsai, 2011).…”
Section: Conceptual Framework For Defining Professional Development Omentioning
confidence: 99%